A theory of distortion of the reaction zone - Coon, Nancy (1980)
A cylindrical detonating explosive behaves like a non-Newtonian viscous fluid emerging from a cylindrical pipe. The expression for non-Newtonian viscous flow has been applied to detonating explosives. The resultant fit to emerging flame fronts from detonation is excellent for a wide variety of detonating explosives both for transients (at various times) and for steady state. The quantities k′(λ/λ(1))(2/B) and 1/B and the rate constant k′ increase abruptly at a time supporting a change in mechanism from deflagration to detonation in the transient during initiation. All of these parameters are temperature sensitive, indicating an abrupt temperature increase as a condition or indicator in the deflagration-to-detonation transition. Furthermore, a straight line results when log particle velocity u is plotted against log radial distance r, indicating that, for the explosives studied, the hyperbolic cosine wave front can be replaced by a parabolic wave front within the accuracy of the available experimental data.